Multiparameter Analysis of the “Off-Target Effects” of Dasatinib on Bone Homeostasis in Patients with Newly Diagnosed Chronic Myelogenous Leukemia - Hoehn, Daniela (Clin Lymphoma Myeloma Leuk, 2016)
We assessed patients with chronic myelogenous leukemia for serum Ca, PO4, bone alkaline phosphatase, N-telopeptide, osteoprotegerin levels and trabecular bone (TBA) in bone marrow (BM) specimens before and after treatment with dasatinib. We identified a significant increase in TBA % in post-dasatinib BM (p=0.022). This suggests that dasatinib therapy can increase TBA, without significant changes in bone and mineral metabolism. INTRODUCTION: Interferences with bone homeostasis and mineral metabolism have been described in patients taking imatinib for chronic myelogenous leukemia (CML) or gastrointestinal stromal tumors. Dasatinib is a potent second generation tyrosine kinase inhibitor (TKI), designed to inhibit ABL and SRC kinases while also interfering with the c-KIT, PDGF-R and STAT5 pathways. PATIENTS AND METHODS: In this study, we use a multiparameter approach to examine the “off target effects” of dasatinib in 30 patients with CML treated between 2009 and 2012. We recorded serum calcium (Ca) and phosphate (PO4) levels, analyzed markers of bone formation (bone alkaline phosphatase/ BAP) and bone resorption (N-telopeptide/NTX), measured osteoprotegerin (OPG) levels and digitally analyzed changes in trabecular bone area (TBA) in paired bone marrow biopsy specimens (BM) before and after treatment. We correlated all findings with each other and with results of conventional cytogenetic and molecular analysis. RESULTS: We identified a significant increase in TBA% in post-dasatinib BM biopsies (p=0.022), and noted a decrease in serum OPG levels in 75% of patients. Ca, PO4, BAP and NTX levels remained steady without significant changes. There was no correlation between biomarker levels, TBA%, and/or cytogenetic/ molecular response. CONCLUSION: These findings suggest that dasatinib therapy (within the therapeutic range) can increase trabecular bone, without causing significant changes in bone and mineral metabolism. Nonetheless monitoring of bone health and skeletal integrity should be included into the long term management of patients treated with dasatinib to further enhance our understanding of its safety profile and potential role as a treatment modality for other bone diseases.